The Influence of Project-Based Learning with a Science Technology Community Approach on Elementary School Social Studies Learning Outcomes - habibi, muhamad ridwan; Yuliani, Meri; Saputra, Tom (JUPE : Jurnal Pendidikan Mandala, 2025)
This study uses a quasi-experimental research methodology with samples in this study, namely class IV, Group A as an experimental class taught with the Project Based Learning Science Technology Society Approach learning model and group B as a control class taught with conventional methods. The results of the study showed that the social studies learning outcomes of students taught with the Project Based Learning learning model (experimental class) were higher than the learning outcomes with conventional methods (control class). The social studies learning outcomes in the control class with the conventional method obtained an average posttest of 68.4 while in the experimental class with the project based learning model obtained an average posttest of 82.4. Based on the results of hypothesis testing in the experimental class, the sig. (2-failed) value was obtained 0.000 <0.05 at a significance level of α = 0.05 means that Ha is accepted and Ho is rejected, which states that the use of the Project based learning model has an effect on improving student learning outcomes in social studies subjects at Sedau 3 Elementary School.